Pengaruh Suku Bunga Dan Risiko Kredit Terhadap Profitabilitas Melalui Efisiensi Operasional Sebagai Variabel Intervening Pada Perusahaan Perbankan Yang Terdaftar Di Bursa Efek Indonesia Periode 2020-2024 - Amirah Fauziah; Elfiswandi Elfiswandi; Putri Intan Permata Sari (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2026)
This study aims to analyze the effect of interest rates and credit risk on profitability with operational efficiency as an intervening variable in banking companies listed on the Bursa Efek Indonesia during the 2020–2024 period. Profitability is measured using Return on Assets (ROA), credit risk is proxied by Non-Performing Loans (NPL), and operational efficiency is measured using the BOPO ratio. This research uses secondary data derived from published annual bank financial statements. The analytical methods applied are multiple linear regression and path analysis using SPSS 23 to test both direct and indirect relationships among variables. The results indicate that operational efficiency has a significant effect on profitability. Interest rates and credit risk influence operational efficiency, but they do not show a significant indirect effect on profitability through the intervening variable. These findings suggest that banks’ ability to control operational costs plays a more dominant role in improving profitability compared to the indirect effects of interest rates and credit risk. This study is expected to provide practical insights for banking management in improving financial performance through stronger operational efficiency strategies.